Perfil bioquímico e eletrolítico, equilíbrio ácido-base e transferência de imunidade passiva de bezerras oriundas de partos eutócicos e distócicos - Luciele de Oliveira Ferreira (2012)
The study had a objective to compare between calves from eutocics and dystocic delivery the biochemical and electrolyte profile, acid-base balance and transfer of passive immunity. A total of 16 Holstein calves, eight born at dystocic and eight born at eutocic, which were evaluated by APGAR score. All animals received the first colostrum two hours after birth and second colostrum at 12 hours after birth. The set times of evaluations were 5 minutes after birth, with two, four, eight, 16, 24, 48 and 72 hours after delivery. To assess the transfer of passive immunity concentrations were determined GGT, total protein by refractometry test, sodium sulfite precipitation and subsequent correlations with the quantification of immunoglobulin G by radial immunodiffusion. Three different tests of sodium sulfite precipitation were evaluated and correlated with immunoglobulin G concentration by radial immunodiffusion. Calves born at dystocic remain with respiratory acidosis longer when compared to animals born eutocics delivery. The transfer of passive immunity was proper regardless of the type of delivery. The refraction test and sodium sulfite precipitation are good methods to evaluate the transfer of passive immunity.